2020
DOI: 10.1021/acsami.9b21385
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Quantum Dot-Based Nanocomposites for Diagnosing Cancer Biomarker APE1 in Living Cells

Abstract: As an essential DNA repair enzyme, apurinic/apyrimidinic endonuclease 1 (APE1) is overexpressed in most human cancers and is identified as a cancer diagnostic and predictive biomarker for cancer risk assessment, diagnosis, prognosis, and prediction of treatment efficacy. Despite its importance in cancer, however, it is still a significant challenge nowadays to sense abundance variation and monitor enzymatic activity of this biomarker in living cells. Here, we report our construction of biocompatible functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 67 publications
(125 reference statements)
0
41
0
Order By: Relevance
“…2 QDs are semiconductor nanocrystals comprised of a core with a diameter ranging typically ranging between 1 and 10 nm and possess high brightness, photostability, 3 broad excitation and narrow and size-tunable emission spectra 4 which render them powerful probes for in vitro and in vivo biomedical imaging applications at the molecular and diagnostic level. [5][6][7] The ability of multiple-sized QDs to be excited by a single wavelength allows efficient multiplexing and the simultaneous detection of various biomarkers in tissue sections, improving the predictability of clinical outcomes. 8,9 Secondly, their high intensity and resistance towards photobleaching permit the longterm tracking of live, single-molecules, which offers detailed information on intracellular trafficking and processing.…”
Section: Introductionmentioning
confidence: 99%
“…2 QDs are semiconductor nanocrystals comprised of a core with a diameter ranging typically ranging between 1 and 10 nm and possess high brightness, photostability, 3 broad excitation and narrow and size-tunable emission spectra 4 which render them powerful probes for in vitro and in vivo biomedical imaging applications at the molecular and diagnostic level. [5][6][7] The ability of multiple-sized QDs to be excited by a single wavelength allows efficient multiplexing and the simultaneous detection of various biomarkers in tissue sections, improving the predictability of clinical outcomes. 8,9 Secondly, their high intensity and resistance towards photobleaching permit the longterm tracking of live, single-molecules, which offers detailed information on intracellular trafficking and processing.…”
Section: Introductionmentioning
confidence: 99%
“…APE1 speci cally cleaves AP site and therefore plays a signi cant role in BER pathway, particularly in the ROS-regulated BER 23 . Abnormal expression and subcellular distribution of APE1 have been linked to tumor development 24,25 . As our previous study, the simple uorescence dequenching of nucleic acid probes can be used for monitoring and quantifying the enzyme activity 26,27 .…”
Section: Resultsmentioning
confidence: 99%
“…The researchers also carried out tests that emphasized the high carrying capacity of the nanosystem, demonstrating its promising application as a bimodal agent in the diagnosis and therapy of cancer. In another study reported by Zhang et al developed a nanocomposite with diagnostic functionality using the apurinic/apyrimidinic endonuclease 1 ( APE1 ) enzyme as a biomarker, as it is overexpressed in most human cancers [ 259 ]. This nanocomposite originated from the unification through adsorption of GQDs and unimolecular DNA architectures acting as a ligand to APE1.…”
Section: Reviewmentioning
confidence: 99%